Functioning in business (California : DynEd International, 1997)
Functioning in businees is a self-paced course for students who need to speak English in the workplace.
System requirements: Windows 95 or Windows NT ; Pentium 90 with 16MB of RAM 640 X 480 with high-color 16-bit display, quad-speed CD-ROM drive 16-bit sound card and microphone
Keywords: Business communication; English language -- Business English; Public speaking